Theme and thematic progression in learner English: a literature review - Wei, Jing (Colombian Applied Linguistics Journal, 2014)
Theme and thematic progression in learner English has been studied extensively. This paper reviews the literature of Theme and thematic progression in learner English. Related articles appearing in the international journals from 1994 to 2013 are gathered and analyzed so that the following four questions can be answered: (i) How can Theme and thematic progression improve coherence in learner English output? (ii) How do English learners deviate from English native speakers in Theme and thematic progression in their output? (iii) What factors contribute to English learners’ deviation in use of Theme and thematic progression? (iv) How can instruction in Theme and thematic progression improve English learners’ use of Theme and thematic progression? Observations are also provided. This review not only provides a synthesis of the related literature in Theme and thematic progression, but also points to issues that could be further addressed in this research area.